Extrovert and Introvert Students’ Problems in Academic Writing - Ali, Sri Widyarti; Husain, Nurlaila N.; Bay, Indri Wirahmi (International Journal of Integrative Sciences, 2025)
Extrovert and introvert students are studied in this case using the study of their personal and learning styles as acquired from their challenges in academic writing. This research has used a descriptive qualitative approach to studying specifically the students with writing difficulties in the English Language Education Study Programme, Class of 2021. Interviews were conducted and then analysed thematically, and key issues identified. Of the 16 students who participated, only one was an introvert, but extrovert students suffer from singular/plural usage, tenses, prepositions, subject/verb agreement, articles, spelling, prefix-suffix, capitalization, punctuation, vocabulary, paragraph Paraphrasing, summarizing, and organization, cohesion and coherence. Like our introvert students, introvert students don’t have subject/verb agreement, articles, capitalization, or paragraph organization problems, but they have similar issues. These problems are influenced by both internal (personality) and external (feedbacks, time, language strategy) factors